Peran Pemda dalam Peningkatan Konektivitas Transportasi Udara di Provinsi Sulawesi Tenggara - Muhamad Rajulan; Maudhy Satyadharma; Hado, Hado (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Air transportation is an important element in supporting regional development, especially in archipelagic areas such as Southeast Sulawesi Province. This study aims to analyze the role of local government in improving air transportation connectivity in the region. The method used is a qualitative approach with purposive sampling techniques of informants who understand air transportation management policies and practices. Data were obtained through interviews, observations, and document reviews during August–November 2024. The results show that the Southeast Sulawesi Regional Government plays a significant role in supporting air transportation connectivity through four main functions, namely as a regulator, dynamizer, facilitator, and catalyst. As a regulator, the local government establishes policies and provides support for land acquisition; as a dynamizer, it encourages collaboration with the private sector; as a facilitator, it bridges cooperation between regions and airlines; and as a catalyst, it accelerates infrastructure development and creates a conducive investment climate. These roles have proven to have a positive impact on increasing mobility, economic growth, and the development of the tourism sector in Southeast Sulawesi. Strengthened collaboration among stakeholders is needed so that air connectivity can function optimally.